New Frontiers in Logistics Research: Theorizing at the Middle Range. Issue 1 (28th February 2017) - Stank, Theodore P.; Pellathy, Daniel A.; In, Joonhwan; Mollenkopf, Diane A.; Bell, John E.
Abstract : Logistics has evolved from a description‐based discipline to one based upon theoretical grounding from other business disciplines to define, explain, and understand complex interrelationships, resulting in the identification of the discipline's primary domain and major concepts—the "what's" of logistics. General theories, however, lack the domain specificity critical to understanding the inner workings within key relationships—the how's, why's, and when's—that drive actual outcomes. Middle‐range theorizing (MRT) enables researchers to focus on these inner workings to develop a deeper understanding of the degree to and conditions under which logistics phenomena impact outcomes as well as the mechanisms through which such outcomes are manifested. This study seeks to spur logistics research at the middle‐range level by presenting a context and mechanism‐based approach to MRT, outlining a process with guidelines for how to theorize at the middle range, and providing a template and examples of deductive and inductive MRT.